EKSISTENSI DAN PENINGKATAN KEMANDIRIAN EKONOMI SANGGAR GONG PRO MELALUI PELATIHAN DIGITAL MARKETING - Ana Sopanah; Hanif Rani Iswari; Firman Nurdiyansyah; Riza Bahtiar Sulistyan (LPPM Universitas Bina Bangsa, 2023)
Problems related to existence and economic independence for activities that are cultural preservation require hard work. This is fully felt by Sanggar Gong Pro which is a studio that dedicates itself to efforts to preserve traditional dance culture. Therefore, academic synergy is needed to realize the existence of Sanggar Gong Pro so that it has economic independence. This synergy is in the form of community service that aims to improve Sanggar Gong Pro's digital marketing capabilities. The methodology includes initial assessment, training, and assistance in creating digital marketing strategies. The result is a significant increase in the digital marketing capabilities of Sanggar Gong Pro managers, increased participant participation, and public awareness about preserving dance culture. This service not only benefits dance studios, but also contributes to cultural preservation and the development of digital marketing competencies in the local community. This illustrates how the potential of digital marketing can support traditional arts and culture in the modern era